2002
DOI: 10.1070/rc2002v071n06abeh000719
|View full text |Cite
|
Sign up to set email alerts
|

Redox reactions of actinides in carbonate and alkaline solutions

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
(100 reference statements)
1
11
0
1
Order By: Relevance
“…There is general agreement that Np(VI) most probably exists in alkaline media as a centrosymmetric anion either NpO 4 (H 2 O) 2 2− or NpO 2 (OH) 4 2− [1,2]. Reported crystal structures of Np(VII) compounds are most consistent with the structurally analogous species NpO 4 (OH) 2 3− as the Np(VII) species that precipitates from alkaline solutions [5][6][7].…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…There is general agreement that Np(VI) most probably exists in alkaline media as a centrosymmetric anion either NpO 4 (H 2 O) 2 2− or NpO 2 (OH) 4 2− [1,2]. Reported crystal structures of Np(VII) compounds are most consistent with the structurally analogous species NpO 4 (OH) 2 3− as the Np(VII) species that precipitates from alkaline solutions [5][6][7].…”
Section: Introductionmentioning
confidence: 82%
“…However, the data available in the literature on oxidation-reduction potentials and speciation are somewhat contradictory and in places are incomplete. For example, Shilov proposes that the hydroxo-complexes NpO 2 OH, NpO 2 (OH) 2 − , NpO 2 (OH) 3 2− , NpO 2 (OH) 4 3− dominate the speciation of Np(V) in basic solutions [2]. Neck, Kim and Kanellakopulos [3], on the other hand, concluded that NpO 2 OH and NpO 2 (OH) 2 − are the only important Np(V) species between pH 7 and 14.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Za njegovu aktivaciju najčešće su potrebne visoke temperature ili oksidansi. Neki od prvih postupaka aktivacije upotrebljavali su kao katalizatore organometalne sustave, [3][4][5][6] metalne ione u plinovitom stanju 7,8 i biokemijske sustave, 9 pri čemu se aktivacija metana može provesti heterogenom, [10][11][12] ili homogenom katalizom. 13,14 Metode izravne pretvorbe dijele se na oksidacijske i neoksidacijske, ovisno o prisutnosti oksidansa.…”
Section: Izravna Pretvorba Metanaunclassified
“…If a solution of 2 M Na 2 CO 3 is used, Am(III) is oxidized with ozone to Am(VI) at room and lower temperatures with an accumulation of Am(V) occurring at higher temperatures. [40][41] In 0.03-0.1M KHCO 3 , Am(V) precipitates as the salt KAmO 2 CO 3 . Without a consideration of the possible complexes that can be formed with americium, the oxidation of Am(III) could be described by the following equations.…”
Section: Task 3 Am/ln Separation With Oxidation State Adjustment Andmentioning
confidence: 99%